Unusual Presentation of Hemophagocytic Lymphohistiocytosis in a Kidney Transplant Patient. (10th March 2019) - Yang, Danwen; Thamcharoen, Natanong; Marcus, Chelsea; Varkaris, Andreas; Aird, William; Khankin, Eliyahu V.; Cardarelli, Francesca
Abstract : We are presenting a case of a middle-aged woman with history of remote kidney transplantation who had multiple admissions for septic shock-like picture, recurrent fever, and hypotension. Her shock manifestation would resolve after stress dose steroid administration and less than 24 hours of vasopressor administration. Initially, extensive workup was performed without revealing etiology. Eventually, a bone marrow biopsy was carried out leading to the diagnosis of hemophagocytic lymphohistiocytosis, most likely related to recent cytomegalovirus infection.